2020
DOI: 10.3390/w12010302
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Land Use/Cover Change on the Hydrological Response of a Southern Center Basin of Chile

Abstract: Several impacts over ecosystem services have been produced by land use/cover changes, placing it as one of the main factors driving global environmental change. In the present study, the SWAT model was used to assess the effect of land use/cover changes on the hydrology response in the Andalien river basin from the south-central zone of Chile. Three land use/cover scenarios (LU_1986, LU_2001, and LU_2011) were compared over a period of 30 years (1984–2013) to remove the effect of climate variability on hydrolo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(20 citation statements)
references
References 73 publications
0
20
0
Order By: Relevance
“…In the worst scenario for winter (SC-3), the hydrological model predicts changes of −2.0%, −2.4% and 8.6% on the base flow, interflow and runoff, respectively. The magnitude of projected changes is comparable to a deforestation scenario in the Vergara River Basin (Stehr et al, 2010), but lower than what was reported in south-central Chile, where changes in LCC are relatively more drastic and different (intensive forestry; Aguayo et al, 2016;Barrientos et al, 2020;Martínez-Retureta et al, 2020).…”
Section: Synergistic Hydrological Effects Between Climate and Lccmentioning
confidence: 49%
See 1 more Smart Citation
“…In the worst scenario for winter (SC-3), the hydrological model predicts changes of −2.0%, −2.4% and 8.6% on the base flow, interflow and runoff, respectively. The magnitude of projected changes is comparable to a deforestation scenario in the Vergara River Basin (Stehr et al, 2010), but lower than what was reported in south-central Chile, where changes in LCC are relatively more drastic and different (intensive forestry; Aguayo et al, 2016;Barrientos et al, 2020;Martínez-Retureta et al, 2020).…”
Section: Synergistic Hydrological Effects Between Climate and Lccmentioning
confidence: 49%
“…Anthropogenic alterations of the natural streamflow regime by way of LCCs make isolating the impacts of climate change on hydrology a daunting task (Yang et al, 2017;Chanapathi and Thatikonda, 2020). In Chile the hydrological impacts of LCCs have been evaluated mainly in south-central Chile (< 41 • S; Stehr et al, 2010;Aguayo et al, 2016;Martínez-Retureta et al, 2020;Barría et al, 2021;Galleguillos et al, 2021) and not in tributary basins to the coastal system of northwestern Patagonia. Nevertheless, using rivers like Puelo River as sentinels, several studies have reported anomalous events in fjords of northwestern Patagonia (e.g., surface hypoxia events, harmful algal blooms), mainly during severe droughts (Valle-Levinson et al, 2007;León-Muñoz et al, 2013Iriarte et al, 2017;Díaz et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Calibration, sensitivity and uncertainty analysis were performed by using the SU-FI-2 algorithm (Sequential Uncertainty Fitting Version 2) [35,36] included in SWAT-CUP (SWAT Calibration, Uncertainty Procedures) [37]. This is a semi-automated reverse modeling procedure that combines and optimizes the modeling parameters for an accurate result [35].…”
Section: Calibration Sensitivity and Uncertainty Analysismentioning
confidence: 99%
“…In Chile, ref. [60] used the Hargreaves-Samani method for PET calculation within a land use change model simulation with SWAT in central-southern Chile. Refs.…”
Section: Introductionmentioning
confidence: 99%